Strengthening Human Capital Through Vocational Education For Inclusive Rural Economic Growth - Nur 'Azah; Mochammmad Syafiuddin Shobirin (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study investigates the role of vocational education in strengthening human capital as a key driver of inclusive rural economic growth. Employing a library research approach, the paper synthesizes scholarly literature, policy reports, and empirical case studies from various regions to analyze how vocational training contributes to enhancing skills, employability, and productivity in rural settings. The analysis highlights that vocational education plays a transformative role in equipping individuals with practical, market-relevant competencies tailored to local economic sectors such as agriculture, agro-industry, crafts, and renewable energy. Moreover, the effectiveness of vocational education is significantly improved when programs are context-specific, inclusive, and supported by strong institutional frameworks, including partnerships among governments, industries, and educational institutions. Special attention is given to how vocational education can address equity issues by reaching marginalized populationssuch as women, youth, and persons with disabilitiesthrough flexible learning modalities and inclusive policies. The study concludes that investing in quality vocational education is essential not only for addressing human capital deficits but also for stimulating inclusive and sustainable economic development in rural areas. Future policy and research efforts should focus on integrating technology, green skills, and local innovation into vocational education frameworks to ensure long-term impact and adaptability.